WHAT MATH STUDENTS NEED TO LEARN ENGLISH? - RAHMATIKA KAYYIS (Politeknik Negeri Bengkalis, 2019)
This research aims to analyse the needs in the process of learning English and to know the specific information about content and material needed by math students. This research is descriptive qualitative and conducted in the third semester of the Mathematics Education Department of STKIP Muhammadiyah Pringsewu Lampung. It was qualitative descriptive research by collecting data from interviews and documentation. The results show that English is important for professional needs because it is needed in all fields. In addition, speaking and grammar are difficult aspects for students. The basic laws of mathematics as materials are needed the most.